Is optoelectronic plethysmography a valid instrument to measure inspiratory capacity? - Danielle Soares Rocha Vieira; Daniele Aparecida Gomes Pereira; Mariana Hoffman Barbosa; Verônica Franco Parreira (Universidade de São Paulo, 2015)
The aim of this study was to evaluate the concurrent validity of the optoelectronic plethysmography (OEP) to measure inspiratory capacity (IC) at rest and during submaximal exercise in healthy subjects. Twelve subjects (6 Male/6 Female; 23.8±1.34 yrs) with normal body mass index and lung function completed the study protocol. Participants were assessed at rest and during a 12-minute submaximal exercise protocol on a cycle ergometer. IC maneuvers were simultaneously recorded by OEP system and by a spirometer at rest and during exercise. The percentage of discrepancy between measurements, linear regression analysis and Bland-Altman method were used for data analysis. The study was approved by the institution ethics committee. It was considered 150 valid IC maneuvers for analysis (44 for resting and 106 for exercise). The percentage of discrepancy between the measurements were -9.6 (8.6%) at rest and -4.6 (5.5%) during exercise. Regression analysis showed good linear associations between methods at rest (r2=0.90; p=0.0002) and during exercise (r2=0.96; p=0.0008). Bland-Altman analysis using data obtained during exercise showed a bias between the two methods of 0.13L. The limits of agreement indicate that the difference between methods can vary from -0.04L to 0.57L. Additionally, data was equally distributed between the upper and lower limits, demonstrating no systematic overestimation or underestimation of the IC by any of the instruments. In conclusion, this study demonstrated that the OEP is a valid evaluation system to measure IC of healthy individuals at rest and during submaximal exercise.